Influence of work environment, workload and job autonomy on job stress among casual dining restaurant employees in the Klang Valley, Malaysia - Amran, Farah Wahida (2019)
Job-related stress is considered a global phenomenon in many industries. Stress at the workplace also happens in the restaurant industry and, stress can affect employee’s job performance and productivity. Stress in the restaurant industry is due to excessive working hours, frequent customer contact, shift hours and physically exhausting. The first aim of this study was to identify the influence and the feeling of job stress. The second aim was to determine the most influential factor and the relationship towards job stress and, lastly, the third aim was to identify the stress level among casual dining restaurant. Three variables were used in this study which are work environment, workload and job autonomy. The primary data were derived from the quantitative method and strictly to Malaysian employees only. A total of 700 self-completed questionnaires were distributed to employees who were currently working in casual dining restaurants in Klang Valley area and 487 usable responses were returned for a 69.6% of response rate. Descriptive and inferential analysis was done by using SPSS version 22. For the first aim, the work environment was found to be the contributor to the job stress with a mean score of 3.74. As for second aim, the two most significant relationship were work environment and workload, F(4, 483) = 28.131, p < .0005, R² = .149. There was no significant relationship by job autonomy. Lastly, most employees were linked to perceived moderate stress level with 84.8%. Also, only a small percentage of respondents perceived high stress level with 5.75%. The limitation of the study was the sample limited to Klang Valley area only. Therefore, it does not represent the whole picture of casual dining employee in Malaysia. Findings obtained in this study also could suggest the casual dining operators strategize ways to minimize stress and ultimately retain their employees in the industry.